Gambaran Kadar Profil Lipid pada Stroke Iskemik - Fariza, Andi F. D.; Rambert, Glady I.; Berhimpon, Siemona L. E. (Universitas Sam Ratulangi, 2025)
Abstract: Stroke is one of the leading causes of death and disability worldwide. Dyslipidemia is one of the risk factors for stroke that can trigger atherosclerosis in blood vessels in the heart as well as in the brain. This study aimed to obtain the lipid profile in patients with ischemic stroke at Prof. Dr. R. D. Kandou Hospital. This was a descriptive and retrospective study using medical records of patients ischemic stroke patients at Prof. Dr. R. D. Kandou Hospital in 2022, using the total sampling method. The results obtained 78 patients that met the inclusion criteria. The highest percentages were found in male patients (56.4%), age group of 56–65 years (42.3%), optimal total cholesterol level (53.8%), low HDL cholesterol level (52.6%), LDL cholesterol level approaching optimal (32.1%), and optimal triglyceride level (62.0%). In conclusion, patients with ischemic stroke most commonly have optimal total cholesterol levels, low HDL cholesterol levels, LDL cholesterol levels approaching optimal, and optimal triglyceride levels. Keywords: lipid profile; ischemic stroke Abstrak: Stroke merupakan salah satu penyebab kematian dan kecacatan di seluruh dunia. Dislipidemia ialah salah satu faktor risiko stroke yang dapat memicu terjadinya aterosklerosis pada pembuluh darah, baik yang berada di jantung maupun otak. Penelitian ini bertujuan untuk mendapatkan gambaran profil lipid pada pasien stroke iskemik di RSUP Prof. Dr. R. D. Kandou. Jenis penelitian ini ialah deskriptif retrospektif menggunakan data rekam medis pasien stroke iskemik di RSUP Prof. Dr. R. D. Kandou tahun 2022 dengan metode total sampling. Hasil penelitian mendapatkan 78 pasien stroke iskemik yang memenuhi kriteria penelitian. Pada hasil analisis didapatkan dominasi pasien berjenis kelamin laki-laki (56,4%), usia 56–65 tahun (42,3%), kadar kolesterol total optimal (53,8%), kadar kolesterol HDL rendah (52,6%), kadar kolesterol LDL mendekati optimal (32,1%), dan kadar kolesterol trigliserida optimal (62,0%). Simpulan penelitian ini ialah pasien stroke iskemik paling banyak ditemukan dengan kadar kolesterol total optimal, kadar kolesterol HDL rendah, kadar kolesterol LDL mendekati optimal, serta kadar kolesterol trigliserida optimal. Kata kunci: profil lipid; stroke iskemik